Impact of subsidies on cancer genetic testing uptake in Singapore. Issue 4 (25th October 2016) - Li, Shao-Tzu; Yuen, Jeanette; Zhou, Ke; Binte Ishak, Nur Diana; Chen, Yanni; Met-Domestici, Marie; Chan, Sock Hoai; Tan, Yee Pin; Allen, John Carson; Lim, Soon Thye; Soo, Khee Chee; Ngeow, Joanne
Abstract : Purpose: Previous reports cite high costs of clinical cancer genetic testing as main barriers to patient's willingness to test. We report findings of a pilot study that evaluates how different subsidy schemes impact genetic testing uptake and total cost of cancer management. Methods: We included all patients who attended the Cancer Genetics Service at the National Cancer Centre Singapore (January 2014–May 2016). Two subsidy schemes, the blanket scheme (100% subsidy to all eligible patients), and the varied scheme (patients received 50%–100% subsidy dependent on financial status) were compared. We estimated total spending on cancer management from government's perspective using a decision model. Results: 445 patients were included. Contrasting against the blanket scheme, the varied scheme observed a higher attendance of patients (34 vs 8 patients per month), of which a higher proportion underwent genetic testing (5% vs 38%), while lowering subsidy spending per person (S$1098 vs S$1161). The varied scheme may potentially save cost by reducing unnecessary cancer surveillance when first-degree relatives uptake rate is above 36%. Findings: Provision of subsidy leads to a considerable increase in genetic testing uptake rate. From the government's perspective, subsidising genetic testing may potentially reduce total costs on cancer management.